2021
DOI: 10.7759/cureus.18083
|View full text |Cite
|
Sign up to set email alerts
|

Rezum Therapy for Benign Prostatic Hyperplasia: Dubai’s Initial Experience

Abstract: IntroductionSymptomatic benign prostatic hyperplasia (BPH) is a condition that affects middle-aged men, leading to a decreased quality of life secondary to symptoms of difficult urination, urinary frequency, urgency and nocturia. The treatment modalities of this pathology include pharmacologic and invasive interventions, both of which vary in effectiveness and they come with a myriad of side effects. Recent advancements have allowed for the development of Rezum, a minimally invasive and effective approach to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The median successful TWOC time was 7 days postoperatively. However, compared with data from other studies (4.1 to 5 days), 11,12 our centre had a longer duration of catheterisation, which could be explained by our centre's policy of scheduling a TWOC on postoperative days 7 and 14 for patients without and with a urethral catheter before surgery, respectively. Five patients were readmitted within 30 days after surgery due to haematuria, post-obstructive diuresis, recurrent AROU, and urinary tract infection with AROU (Table 2).…”
Section: Discussionmentioning
confidence: 52%
“…The median successful TWOC time was 7 days postoperatively. However, compared with data from other studies (4.1 to 5 days), 11,12 our centre had a longer duration of catheterisation, which could be explained by our centre's policy of scheduling a TWOC on postoperative days 7 and 14 for patients without and with a urethral catheter before surgery, respectively. Five patients were readmitted within 30 days after surgery due to haematuria, post-obstructive diuresis, recurrent AROU, and urinary tract infection with AROU (Table 2).…”
Section: Discussionmentioning
confidence: 52%
“…Rowaiee et al 37 reported a significant postoperative increase in Qmax of 8.11 ml/s and a mean decrease of 94.32 cm 3 in prostate volume in their study.…”
Section: Discussionmentioning
confidence: 62%
“…Ines et al evaluated the data of 179 patients aged 45 years and older, with an IPSS score of ⩾8, prostate volume between 20 and 120 cc, with a follow-up of at least 12 months. 35 Garden et al 36 shared data from 36 patients with prostate volume above 80 g and 168 patients below 80 g, while Rowaiee et al 37 retrospectively analyzed data from 49 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, 30–50% of men over 50 years and 80% of men over 80 years suffer from moderate to severe LUTS due to BPH [ 17 ]. TURP is still considered the gold standard medical treatment but is associated with numerous adverse events [ 18 ]. Some vaporization of the prostate by laser or plasma vaporization has been shown to have no significant differences in treatment outcomes and postoperative complication rates [ 19 ].…”
Section: Discussionmentioning
confidence: 99%